2010
DOI: 10.1073/pnas.1008754107
|View full text |Cite
|
Sign up to set email alerts
|

Oil sands development contributes elements toxic at low concentrations to the Athabasca River and its tributaries

Abstract: We show that the oil sands industry releases the 13 elements considered priority pollutants (PPE) under the US Environmental Protection Agency's Clean Water Act, via air and water, to the Athabasca River and its watershed. In the 2008 snowpack, all PPE except selenium were greater near oil sands developments than at more remote sites. Bitumen upgraders and local oil sands development were sources of airborne emissions. Concentrations of mercury, nickel, and thallium in winter and all 13 PPE in summer were grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
370
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(389 citation statements)
references
References 17 publications
17
370
2
Order By: Relevance
“…Some of these constituents include high levels of salinity, sulphate, ammonia, conductivity, and naphthenic acids [6]. There is the potential for some of these components to make their way into the Athabasca River through seepage and air deposition [7]. Previous research has shown that the highest concentrations of sodium and chloride along the Athabasca River mainstem occurred in the mouth reach of the river basin [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these constituents include high levels of salinity, sulphate, ammonia, conductivity, and naphthenic acids [6]. There is the potential for some of these components to make their way into the Athabasca River through seepage and air deposition [7]. Previous research has shown that the highest concentrations of sodium and chloride along the Athabasca River mainstem occurred in the mouth reach of the river basin [8].…”
Section: Introductionmentioning
confidence: 99%
“…The RAMP program focuses on surface waters affected by surface mining operations, and its results and conclusions were thrown into doubt by the detailed analyses of Kelly et al (2009Kelly et al ( , 2010. This paper is not the place to review the criticisms of the RAMP program, which were documented by Ayles et al (2004) This summary paper draws extensively on the above mentioned reports, and other studies prepared by or for the Cumulative Environmental Management Association and the Oil Sands Research and Information Network.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Kelly et al (2009Kelly et al ( , 2010 and Kurek et al (2013) (see summary by Schindler, this issue) make it clear that the most significant source of industrial pollution in the Athabasca system consists of airborne pollutants from the processing and upgrader facilities, which may settle out into lakes and the rivers up to about 100 km from source (see Percy 2013). Some of this pollutant could be carried into the shallow groundwater system from uplands that act as local recharge areas.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kelly et al [13] measured greater mercury concentrations in water and snow near oil sands developments compared to locations further removed from developments. On the other hand, Wiklund et al [14] note that, since the 1990s, increasing Canadian oil sands industrial development does not coincide with the decreasing trend in mercury concentrations in sediment cores downstream of the oil sands region.…”
Section: Introductionmentioning
confidence: 99%